Narrativizing Intramuros: A Counterdiscourse to Neocolonialism - Devilles, Gary C. (Archīum Ateneo, 2024)
This article is a textual analysis of two short stories of Pedro S. Dandan who has articulated for Filipinos their political unconscious against the onslaught of colonial domination. In his works we read how Filipinos confront socio-political problems of war, squatting, poverty in everyday lives. Since most of his stories depict Manila in its early phase of urbanization, it is interesting to note how such stories offer a crucial perspective to the real socio-political problems we are still experiencing today. Reading his works in light of our contemporary problems will reveal the various interplay of forces of control and resistance. Dandan’s short stories narrativize these forces and allow us to see how problems are assessed and reassessed. Conveniently, Dandan’s stories are narrativization of our roles as subjects in a continued effort for improvement and further emancipation. In the works of Dandan, we pose also the question of who we are in relation to this domination and how we can recognize ourselves as agents of transformation in our society. These articulations have generative resonances to our own real situation and condition. In this paper, Intramuros is not only a convenient setting in Dandan’s stories, rather Intramuros becomes the narrative of Filipinos’ colonial experience and counter-colonial sentiments.